'Whoever has will be given more' (Matthew 13:12): authorship of systematic reviews and clinical trials in the biological age. (June 2017) - Stern, R.S.
Abstract : Linked Article:Gómez‐García et al. Br J Dermatol 2017;176 :1633–1644 . Tauber and Paul. Br J Dermatol 2017;176 :1669–1671 .